The effect of granular BRA modifier binder on the stiffness modulus of modified asphalt - Karami, M.; Nikraz, Hamid (2015)
© 2015 Taylor & Francis Group, London.This study is aimed to evaluate the effect of using a granular Buton RockAsphalt (BRA) modifier binder for improving the stiffness modulus performance of asphalt mixtures. The stiffness moduli of BRA modified asphalt mixtures and unmodified asphalt mixtures (as control mixtures) for a dense grading of 10mm were determined using an Indirect Tensile Stiffness Modulus (ITSM) test at five different temperatures (5, 15, 25, 40, and 60?C), three different rise times (40, 60, and 80 ms), and three pulse repetition periods (1000, 2000, and 3000 ms). Results from this study indicated that stiffness moduli for BRA modified asphalt mixtures were higher than that for control mixtures at any test temperature, rise time, and pulse repetition period. The change in temperature is the biggest influence on changing the stiffness modulus compared to the change in rise time and the pulse repetition period for both asphalt mixtures.